Diagnosis and management of a rare case with placental site trophoblastic tumor - Fu-Nan Cho; San-Nung Chen; Yu-Hsiang Chang; James R. Carey (Elsevier, 2016)
Objective: Placental site trophoblastic tumor (PSTT) is rare and is characterized by a slow growth. The objective of this report is to present a case of PSTT associated with irregular vaginal spotting that occurred 1 year after normal vaginal delivery. Case Report: This report provides interesting ultrasound, hysteroscopy, and histology findings of PSTT. It is difficult to make a clinical diagnosis of PSTT at an early stage. Without the use of immunohistochemical analysis, PSTT may evade histological detection. An operative hysteroscopy using electrocauterization reduces active bleeding during the removal of PSTT with markedly engorged tumor vessels. Conclusion: Transvaginal sonography using color Doppler imaging plays a vital role in identifying residual PSTT with microscopic infiltration to the myometrium and a negative serum β-human chorionic gonadotropin level.